Differential Relationship between Intermuscular Adipose Depots with Indices of Cardiometabolic Health - Robert E. Bergia; Jung Eun Kim; Wayne W. Campbell (International Journal of Endocrinology)
Background. Globally, accumulation of intermuscular adipose tissue (IMAT) is positively associated with insulin resistance. Whether this association is observed consistently in different skeletal muscles and encompasses other markers of cardiometabolic health is not well known. Objectives. The purpose of this secondary analysis study was to investigate associations among thigh or calf IMAT stores and indices of cardiometabolic health in adults who are overweight and obese participating in dietary interventions. A subset of calf data was analyzed to assess relations between IMAT in the gastrocnemius (type II fiber predominance) and soleus (type I fiber predominance) with markers of cardiometabolic health. Materials and Methods. Thigh and calf compositions were assessed via magnetic resonance imaging in 113 subjects (mean ± SD, age: 50 ± 16 y (range: 21–77 y), BMI: 31 ± 3 kg/m2), 103 of which completed dietary interventions with or without energy restriction-induced weight loss. A subset of data (n=37) was analyzed for relations between muscle compartments (gastrocnemius and soleus) and cardiometabolic health. IMAT was regressed separately against fasting serum glucose concentrations, insulin, homeostatic model assessment-insulin resistance (HOMA-IR), and lipids and lipoproteins. Results. In general, total thigh IMAT was predictive of markers of glucose control, while total calf IMAT was not. Specifically, baseline thigh IMAT was positively associated with fasting glucose, insulin, and HOMA-IR. IMAT content changes in any depot did not predict improvement in cardiometabolic health. Conclusions. The strength of the relationship between IMAT and glucose control-related indices of cardiometabolic health is dependent on IMAT location. Specifically, greater IMAT in the thigh is a better predictor of cardiometabolic risk than greater IMAT in the calf in adults who are overweight and obese.